Exascale models of stellar explosions: Quintessential multi-physics simulation. (January 2022) - Harris, J. Austin; Chu, Ran; Couch, Sean M; Dubey, Anshu; Endeve, Eirik; Georgiadou, Antigoni; Jain, Rajeev; Kasen, Daniel; Laiu, M P; Messer, OE B; O'Neal, Jared; Sandoval, Michael A; et al.
The ExaStar project aims to deliver an efficient, versatile, and portable software ecosystem for multi-physics astrophysics simulations run on exascale machines. The code suite is a component-based multi-physics toolkit, built on the capabilities of current simulation codes (in particularFlash-X andCastro ), and based on the massively parallel adaptive mesh refinement frameworkAMReX . It includes modules for hydrodynamics, advanced radiation transport, thermonuclear kinetics, and nuclear microphysics. The code will reach exascale efficiency by building upon current multi- and many-core packages integrated into an orchestration system that uses a combination of configuration tools, code translators, and a domain-specific asynchronous runtime to manage performance across a range of platform architectures. The target science includes multi-physics simulations of astrophysical explosions (such as supernovae and neutron star mergers) to understand the cosmic origin of the elements and the fundamental physics of matter and neutrinos under extreme conditions.